Celastrus Paniculatus, An Endangered Indian Medicinal Plant With Miraculous Cognitive And Other Therapeutic Properties: An Overview - NEHA ARORA; SHASHI PANDEY-RAI (International Journal of Pharma and Bio Sciences, 2012)
Celastrus paniculatus is an Indian medicinal plant which has been used for thousands of years in the traditional Ayurvedic system of medicine. It is fast gaining importance in the primary healthcare systems as well as in herbal drug formulations. Oil obtained from the seeds of the plant is reported to be highly beneficial in stimulating intellect and sharpening the memory. It also acts as a potential nervine tonic, rejuvenator and an anti-depressant. Moreover, the plant possesses a strong antioxidant as well as free radical scavenging activity. C. paniculatus has also been exploited for its potential role in the management of neurodegenerative diseases and other neuronal disorders such as Alzheimer’s disease. Oil being a powerful stimulant for neuromuscular system is also used for the treatment of rheumatism, gout and paralysis. This review aims at exploring the detailed phytochemical composition, pharmacological properties as well as therapeutic applications of different parts of C. paniculatus.